ETIOLOGY FOR LIVER DISEASES IN PEDIATRIC POPULATION - Karakkattu, Jismy; Pr, Roshni (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The liver diseases affect both the pediatric and adult populations. In the adult population, the stereotype diagnosis in the Indian population is targeted toward males due to excessive alcoholic consumption. Nevertheless, the liver diseases can also affect both the female and pediatric populations. Pediatric liver diseases include cirrhosis, fatty liver diseases, and hepatic failure. The liver diseases are commonly caused by biliary atresia and genetic metabolic diseases. In children, the signs and symptoms of liver diseases are dependent on the principal reason of the liver disease. This review article is to cover all the etiologies that have been identified to cause liver diseases with a special focus on pediatric acute liver failure. Methods: An extensive PubMed search was conducted and articles that were published after 2007 were included in this article. Results: The pediatric population etiology of liver diseases can be broadly categorized into infections, immunologic, metabolic, toxin or drug related, indeterminate, and diseases resulting in liver cirrhosis. Complications of pediatric liver diseases include malnutrition, infection, gastroesophageal varices, and hepatic encephalopathy. Conclusion: Overall, the etiology for liver diseases in the pediatric population is many. Early identification of these factors can improve the quality of life of the pediatric patient. With the correct diagnostic parameters and treatment certain conditions can be completely cured. As for those whose effective treatment is still lacking it is essential to continue the ongoing research until the missing pieces have been identified. Keywords: Pediatric population, Liver diseases, Acute liver failure, Etiology, Pediatric acute liver failure.